The Agency Advantage of Debt over the Lifecycle of the Firm - Ed Vos; Carolyn Forlong (Journal of Entrepreneurial and Small Business Finance, 1996)
The question of an `optimal' capital structure of a firm has been studied for publicly listed businesses for years. From these studies, agency theory has emerged as a good way to understand a firm's capital structure. This paper empirically examines the role that agency theory plays in determining the capital structure of businesses as they move from being small unlisted businesses to newly listed on the stock exchange, to being mature listed businesses. The paper finds that debt has a negative agency advantage (defined as reducing agency costs of equity) for small businesses, a significant but minor advantage at the IPO stage, and a significant advantage at the mature listed stage.
Keywords: G32; M13; 650; Agency; Debt; Lifecycle